Tamsulosin versus Alfuzosin as medical therapy for ureteric stones - B Piya (Society of Surgeons of Nepal, 2016)
Objectives: To evaluate and compare the efficacy of tamsulosin and alfuzosin as medical therapy in ureteric stones.